The Economics of the Global Stock Exchange Industry - Floreani, Josanco; Polato, Maurizio; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book is an economic analysis of the stock exchange industry. The authors draw on theories from micro- and industrial economics to provide a detailed analysis of the industry structure, the strategic behaviour of key participants and the performance of stock exchanges.
Keywords: Stock exchanges; Stock exchanges -- Law and legislation; Securities industry